Student Feedback on Teaching Methods in Professional Speaking Contexts - Sujariyati, Sujariyati; Pangalinan, Markus Rano (Publikasi dan UKI Press UKI Toraja., 2024)
This study examines student perceptions of teaching methods in Professional Speaking for Context courses at SMPN 1 Buntu Pepasan Toraja Utara, focusing on instruction clarity, engagement, effectiveness of teaching aids, opportunities for practice, and overall satisfaction. The research utilized surveys, focus group discussions, and interviews to gather data from students about their experiences and opinions. The results indicate that a majority of students find the clarity of instruction effective, with 75% reporting that guidelines are generally clear and helpful, though some students experience occasional confusion. Interactive activities such as group discussions and presentations were praised for enhancing engagement, although 40% of students desired more varied instructional methods to maintain interest. Teaching aids like slides and videos were beneficial for understanding, yet technical issues occasionally disrupted learning. Despite ample practice opportunities, 30% of students called for more personalized feedback to improve their speaking skills. Overall, while the majority of students expressed high satisfaction with the teaching methods, there is room for improvement in diversifying teaching approaches, addressing technical problems, and providing individualized feedback. These findings suggest that refining these aspects could lead to a more effective and engaging learning environment.